Psychological research and practice in former Yugoslavia and its successors. Issue 1 (30th September 2022) - Pajić, Dejan; Biro, Mikloš
Abstract: This paper presents a brief history of Yugoslav psychology and a review of the current state of psychological research and practice in the former Yugoslav countries. Bibliometric mapping was used to explore the knowledge domain and international visibility of psychological research in Bosnia and Herzegovina, Croatia, North Macedonia, Montenegro, Serbia, and Slovenia. Judging by the number of papers visible in Scopus, psychological research activity in these countries is similar to the other former communist countries. In a relative sense, it is even higher in Slovenia and Croatia. However, psychologists still rely heavily on national journals indexed in Scopus when publishing their papers. Regarding psychological practice, former Yugoslav countries are facing challenges that are more or less typical for all small countries in the global scientific and economic market. Keeping in mind all the obstacles and traumas in the past decades, it should be considered a success that psychology in the former Yugoslav countries is now a fully established profession and a recognized scientific discipline.